THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF PSYCHOLOGICAL STABILITY PROBLEMATICS OF THE ARMED FORCES OF UKRAINE PERSONNEL CONDITIONED BY THE RUSSIAN FEDERATION ARMED AGGRESSION - Kravchenko, K. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The subject of this article is framed by the current threats and challenges, namely the conduct of hostilities in eastern Ukraine and disappointing predictions about the potential start of a full-scale offensive of Russian troops on our country. In such circumstances, it can be argued that the issue of psychological stability of the Armed Forces of Ukraine is important, relevant and urgent in its solution. It should be noted that the psychological resilience of the personnel of the Armed Forces of Ukraine (and other law enforcement agencies) is one of the important factors in the reliability and effectiveness of activities during hostilities and the impact of other various hybrid threats. The purpose of the article is to analyze the scientific developments, their generalization and substantiation of the necessary recommendations for improving the existing system of formation, provision and restoration of psychological stability of the personnel of the Armed Forces of Ukraine. Considering the issue of psychological stability of the Armed Forces of Ukraine, the authors of the article set themselves the following tasks: 1) to summarize the views of domestic and foreign researchers on psychological stability as a subject of research; 2) to determine the set of stress factors in relation to which it is necessary to form the psychological stability of the personnel of the Armed Forces of Ukraine; 3) consider the structure of psychological stability; 4) to analyze the features of the formation of psychological stability; 5) propose methods for assessing psychological resilience; 6) provide methodological recommendations for the formation and maintenance of psychological stability in modern hybrid threats.